Design of a Simple Inductor-less AC-AC Converter Realizing High Input Power Factor - Kei Eguchi; Wanglok Do; Kanji Abe; Krit Smerpitak; Sawai Pongswatd (My University, 2017)
Switched capacitor (SC) techniques is used in order to design a simple inductor-less ac-ac converter with small size and high input power factor. Comparing conventional inductor-less ac-ac converters with the proposed converter, an input/ output (I/O) terminal is connected alternately to one of capacitors to achieve ac-ac conversion. To realize the new topology, the new designed converter is composed of two capacitors and four switches in the conversion ratios of 2 and 1/2. For this reason, as well as high input power factor, the proposed converter can achieve small size. To explain how the proposed converter is operated with the conversion ratios of 2 and 1/2, operation’s law, analysis in theory, and results of circuit simulation are written on this paper. The validity of the proposed converter is confirmed by circuit simulations using SPICE simulator. Keywords: Direct AC-AC Converters, Power Converters, Switched Capacitor Techniques, Switching Mode Power Supply
Keywords: Switched capacitor; Buck converter; Advanced DC-DC Converters